A Young Man with Multiple Skin Lesions on a Positron Emission Tomography-Computed Tomography Scan - Gür, Mert Berke; Toker Dinçer, Zeynep; Melikoğlu, Melike; Seyahi, Emire (Cerrahpaşa Medical Journal, 2025)
Cite this article as: Gur MB, Toker Dincer Z, Melikoglu M, Seyahi E. A young man with multiple skin lesions on a PET-CT scan. Cerrahpaşa Med J 2025, 49, 0070, doi: 10.5152/cjm.2025.24070.